Effect of Residue Management, Row Spacing, and Seeding Rate on Winter Canola Establishment, Winter Survival, and Yield - B. M. Showalter; K. Roozeboom; M. J. Stamm; R. Figger (Kansas Agricultural Experiment Station Research Reports, 2017)
Winter survival of canola (Brassica napusL.) is a challenge for producers using high-residue, no-tillage, or reduced-tillage systems. An innovative residue management system being developed by AGCO Corporation was compared to cooperating canola producers’ residue management and planting methods in wheat stubble. This series of on-farm experiments was conducted in 2014-2015 and 2015-2016 at ten locations in central and south-central Kansas. The AGCO treatments were 20- or 30-in. row spacing and three seeding rates (100,000, 150,000, and 200,000 seeds/a) for a total of six treatments. The producer treatment at each location included row spacing, seeding rate, and residue management practices preferred by that producer. Due to winter stand loss, only one of the six experiments planted in the fall of 2014 was harvested for yield in 2015. All four experiments planted in fall 2015 were harvested for yield in 2016. Fall stands usually differed in response to seeding rate and often were greater in 20-in. rows than in 30-in. rows. Spring stands were not as tightly correlated with seeding rate, but were consistently greater in narrow rows, regardless of seeding rate and residue management practices. Winter survival increased with reductions in seeding rate at most locations and was greater in 20-in. rows than in 30-in. rows at three of the five harvested locations. Yields were not affected by residue management, row spacing, or seeding rate at two of the five locations, including the location with yields surpassing 60 bu/a. At the other three locations, yields with the AGCO residue management system equaled or exceeded yields obtained with cooperator practices that typically included much greater seeding rates. Yields seldom responded to seeding rate, but when they did, yields tended to increase as seeding rate decreased.
Keywords: canola; seeding rates; residue management; row spacing